Correction of cellular and humoral links immunity in piglets under the weaning condition - Nataliia Ohorodnyk; Vitalii Tkachuk; Nataliia Motko; Andriy Boyko; Serhii Pavkovych (Наукові горизонти)
Preventing the development of immunodeficiencies in piglets after weaning is achievable through the parenteral administration of fat-soluble vitamins, macroand microelements, and by analysing their effects on the dynamics of changes in the number and functional activity of T- and B-lymphocyte subpopulations. Accordingly, this study aimed to investigate the effect of a complex liposomal preparation on the cellular and humoral components of the piglet immune system after weaning. A standardised methodology was used to determine the number of different populations and subpopulations of T-lymphocytes in piglet blood samples collected before and at specific intervals after weaning. The analysis of the quantitative composition of T- and B-lymphocytes and the functional activity of T lymphocytes in the blast transformation reaction was conducted using immersion microscopy of smears. The statistical processing of results was carried out through variational nonparametric analysis using biometric methods. The findings revealed that weaning from sows caused a reduction in the number of T-cells of varying degrees of avidity, a decrease in the relative number of T-suppressors in piglets’ blood, and an increase in the number of certain subpopulations of T-helper cells. Conversely, the administration of the liposomal preparation to piglets enhanced the number of various subpopulations of total and active T-lymphocytes and B-lymphocytes in their blood after weaning and increased the activity of lymphoid cells in the blast transformation reaction with phytohaemagglutinin. The observed immunomodulatory effect of the tested drug is attributed to the synergistic combination of fat-soluble vitamins, mineral elements, and arginine in its composition, which effectively prevented the development of stress-induced immunodeficiency in piglets following weaning